Larvicidal, Histopathological Efficacy of Penicillium daleae against Larvae of Culex quinquefasciatus and Aedes aegypti Plus Biotoxicity on Artemia nauplii a Non-target Aquatic Organism - Ragavendran, C.; Mariappan, T.; Natarajan, Devarajan (Frontiers in Pharmacology, 2017)
Mosquitoes can transmit the terrible diseases to human beings. Soil-borne fungal products act as potential source for low-cost chemicals, used for developing eco-friendly control agents against mosquito-vector borne diseases. The prime aim of study was to check the larvicidal potential of fungus mycelia (by ethyl acetate solvent) extract from Penicillium daleae (KX387370) against Culex quinquefasciatus and Aedes aegypti and to test the toxicity of brine shrimp Artemia nauplii, by observing the physiological activity. The ethyl acetate extract of P. daleae mycelia (after 15 days) from Potato dextrose broth (PDB) medium revealed better result with least LC50 and LC90 values of I-IV instars larvae of Cx. quinquefasciatus (LC50=127.441, 129.087, 108.683, 93.521; LC90=152.758, 158.169, 139.091,125.918 µg/ml) and Ae. aegypti (LC50=105.077, 83.943, 97.158, 76.513; LC90= 128.035, 106.869, 125.640, 104.606 µg/ml) respectively. At higher concentration (1000 µg/ml) of extracts, mortality begins at 18 h of exposure and attained 100 % mortality after 48 h exposure. Overall, the activity was depends on the dose and time of exposure to the extracts. The stereomicroscopic and histopathological analysis of Ae. aegypti and Cx. quinquefasciatus larvae treated with mycelium ethyl acetate extract showed complete disintegration of abdominal region, particularly the midgut and caeca, loss of cuticular parts and caudal hairs. Morphological characterization of the fungi was performed and taxonomically identified through 5.8s rDNA technique. The phylogenetic analysis of rDNA sequence was carried out to find out the taxonomic and the evolutionary sketch of isolate in relation to earlier described genus Penicillium. Behaviour and swimming speed alteration was analyzed together with mortality. The results of the experiment indicates that Swimming behaviour recorder (SBR) is a appropriate tool to detect individual swimming speed of the Artemia nauplii organisms, since the values have been obtained in accordance with control monitored results showed the 2.75 mm s-1 and after 24h treated found to be 0.72 mm s-1, respectively. The extract-exposed to A. nauplii showed changes in body structures i.e, intestine enlargement, eye formation, outer shell malformations and loss of antennae. In the present study, we aimed to investigate the toxicity of the ethyl acetate extract of P. daleae on A. nauplii larvae